IMPACT OF NON-VERBAL COMMUNICATION ON MASKS IN DAHA ATA SANNIYA RITUAL (Proceeding of the International Conference on Arts and Humanities, 2019)
Non-verbal communication is anything other than words themselves that communicates or affects (positively or negatively) the message "contained" in the words. (Dr. K Sharma Vipin,2011, Decoding Non-Verbal Communication).The objective of this study is  to  identify the Effectiveness of non verbal communication in  mask that uses in rituals in Sri Lanka. In  order to achieve the objectives, a qualitative analysis was done using Primary data and  secondary data which collected based on law country dance ritual of Daha Ata Sanniya. According to the sample researcher gathered data from 15educators of traditional dance and audience of the Daha Ata Sanniya by conducting focused interviews and discussions with them. The finding shows that visual excitement in mind and colors that used in mask, Ayurveda medicine methods convey the massages of cultural values and concepts in the society. The size of a mask has been decided character’s personality. The manner in which facial expressions are displayed is influenced by the following factors: social factors, emotional factors, expression of personality and physiological factors which include manipulators, pain, tiredness, physical variables and facial reflexes such as sneezing, nasal membrane irritation, pupillary dilation to pain, joy closure to tap, yawning and laughter (Fridlund, 1994).
Keywords: Non verbal communication; Ritual; colors in Mask; cultural values and concepts